If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 = 3 + -1(z + 10) Reorder the terms: 15 = 3 + -1(10 + z) 15 = 3 + (10 * -1 + z * -1) 15 = 3 + (-10 + -1z) Combine like terms: 3 + -10 = -7 15 = -7 + -1z Solving 15 = -7 + -1z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add 'z' to each side of the equation. 15 + z = -7 + -1z + z Combine like terms: -1z + z = 0 15 + z = -7 + 0 15 + z = -7 Add '-15' to each side of the equation. 15 + -15 + z = -7 + -15 Combine like terms: 15 + -15 = 0 0 + z = -7 + -15 z = -7 + -15 Combine like terms: -7 + -15 = -22 z = -22 Simplifying z = -22
| 8n+12=3n+18 | | 4x+12=3x-12 | | B-18=(-13) | | 5x-1=x+6 | | -12q+n=-29 | | f(x)=x^2-4x-8 | | 11n=198 | | 2x+7y=6(x+y) | | 12=12+8y | | 5+n=-12 | | 8n+12=3-n+18 | | x+(-20)=-18 | | 6x^2+15x-37=0 | | 3(2x+2)=5(x+1) | | 3cos^2x+7sinx=5 | | 8n+12=-3n+18 | | 20x-40=-80 | | 13+m=-1 | | 2k-6=8+k | | 6a-4+2=3a+1a | | db+x=9(b-d) | | -8b-(-2b)= | | 18x+5-1+8x=46 | | 9n-5=-29+3n | | p-(-11)=11 | | 4z-22=-26+8z | | -6x-32=2 | | 12=9x+3+6 | | p+1=16 | | 60x+75y=9 | | -8+n=-7 | | (-11)-w=(-36) |